The factorization of the expression by grouping is [tex]P(x) = (x - 3)(x + 3)(x +4)[/tex]
The polynomial function is given as:
[tex]P(x) = x^3 + 4x^2 - 9x - 36[/tex]
Factorize the given expression.
[tex]P(x) = x^2(x + 4) - 9(x +4)[/tex]
Factor out x + 4
[tex]P(x) = (x^2 - 9)(x +4)[/tex]
Express 9 as the square of 3
[tex]P(x) = (x^2 - 3^2)(x +4)[/tex]
Apply the difference of two squares
[tex]P(x) = (x - 3)(x + 3)(x +4)[/tex]
Hence, the factorization of the expression by grouping is [tex]P(x) = (x - 3)(x + 3)(x +4)[/tex]
Read more about factorization at:
https://brainly.com/question/11434122